Dissenting Opinions in the Jurisprudence of Collegial Public Finance Bodies in Poland. Documentary Research - Kowalski, Patryk; Bogucka-Felczak, Monika; Budziarek, Magdalena; Kapusta, Monika (PRAWO i WIĘŹ, 2025)
The purpose of this paper was to examine the practical operation of the concept of dissenting opinions submitted to decisions of collegial public finance bodies (joint adjudicating committee, inter-ministerial adjudicating committees, adjudicating committee at the Chief of Staff of the Prime Minister Chancellery, regional adjudicating committees at regional accounting chambers, the Main Adjudicating Committee, local government appeal boards) between 2004 and 2020. The research was conducted using the empirical legal studies method and the dogmatic method. The research material included an analysis of 42 proceedings (16 different factual and legal situations) in which judgments with a dissenting opinion were issued. This led to the following research conclusions: the number of dissenting opinions submitted to the decisions of collegial public finance bodies is small; the largest number of dissenting opinions was issued in cases of violation of public finance discipline resulting from the violation of public procurement regulations; the procedural function of dissenting opinions submitted to the decisions of collegial public finance bodies is very rarely used, in 81% of the examined cases the dispute in the adjudicating panel concerned only the interpretation of the law.